Notes on the spider genus Segestria Latreille, 1804 (Araneae: Segestriidae) in the East Palaearctic with description of three new species - Fomichev, Alexander A.; Marusik, Yuri M. (Zootaxa, 2020)
Three new species of Segestria Latreille, 1804 are described from the East Palaearctic: Segestria nekhaevae sp. n. (♀, Tajikistan), S. shtoppelae sp. n. (♂♀, Kazakhstan), and S. fengi sp. n. (♂♀, China). Two other species found in Asia, S. turkestanica Dunin, 1986 (Central Asia) and S. nipponica Kishida, 1913 (Japan) are illustrated. Segestria is reported for the first time from Kazakhstan and Tajikistan.